A Comparison of Hot Pack and Stretching Exercises on Primary Dysmenorrhea in Adolescent Girls - Farahdina Bachtiar; Andi Rabiatul Mahbuba Mursyid; Salki Sadmita (Faculty of Nursing, Universitas Hasanuddin, 2019)
Introduction: Dysmenorrhea or menstrual cramps is a pain (usually in the pelvis, lower back or abdomen) during menstruation. The pain usually begins several days before or during menstrual bleeding starts. It is often mild but in some cases, the symptoms may be more painful and cause discomfort. Dysmenorrhea is divided into two categories including primary (not associated with pelvic pathology) and secondary (resulting from underlying diseases) dysmenorrhea. The purpose of this study was to compare the effect of hot pack and stretching exercises on pain in adolescent girls with primary dysmenorrhea. Method: This was an experimental research with two group pre-test and post-test design. Twenty girls of students in Class X who met the inclusion and exclusion criteria were assigned in two groups: hot pack (n=10) and stretching exercise groups (n=10). The menstrual pain was measured using the Visual Analogue Scale (VAS) before and after six times interventions. The pain score changes in each group were analysed using paired sample test while the comparison means for hot pack and stretching groups were assessed using independent samples t-test. Result: The results revealed that the intensity of the pain in both hot pack and stretching exercises group were declined (p <.05). After conducting independent sample t-test, it was found that there was a statistically significant difference between the level of pain for the hot pack and stretching group (p = 0,001). Conclusion: Hot pack is more effective in reducing dysmenorrhea (menstrual pain) compare to stretching exercises.